On the Influence of Structural Connectivity on the Correlation Patterns and Network Synchronization - Nazemi, Parisa Sadat; Jamali, Yousef (Frontiers in Computational Neuroscience, 2019)
Background: Since brain structural connectivity is the foundation of its functionality, in order to understand the brain abilities, studying the relation between structural and functional connectivity is essential. Several approaches have been applied to measure the role of the structural connectivity in the emergent correlation/synchronization patterns. In this study, we indicate a link between the brain structural connectivity and its functional organization. Method: This paper investigates the cross-correlation and synchronization sensitivity to coupling strength between neural regions for different network topologies. We model the neural populations by a neural mass model that expresses an oscillatory dynamic. Results: The results highlight that the coupling between neural ensembles leads to various cross-correlation patterns and local synchrony even on an ordered network. Moreover, as the network departs from an ordered organization to a small-world architecture, correlation patterns and synchronization dynamics change. Interestingly, at a certain range of the synaptic strength, by fixing the structural conditions, different organized patterns are seen at the different input signals. This variety switches to a bifurcation region by increasing the synaptic strength. Conclusion: We show that topological variation is a major factor in the synchronization behavior and leads to alterations in the correlated local clusters. We found the coupling strength (between cortical areas) to be especially important at the conversions of correlation and synchronization states. Since correlation patterns generate functional connections and transitions of functional connectivity have been related to cognitive operations, these diverse correlation patterns may be considered as the different dynamical states corresponding to the various cognitive tasks.